2016
DOI: 10.3389/fmicb.2016.00682
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Actin Cables in Polarized Growth of the Filamentous Fungus Aspergillus nidulans

Abstract: Highly polarized growth of filamentous fungi requires a continuous supply of proteins and lipids to the hyphal tip. This transport is managed by vesicle trafficking via the actin and microtubule cytoskeletons and their associated motor proteins. Particularly, actin cables originating from the hyphal tip are essential for hyphal growth. Although, specific marker proteins have been developed to visualize actin cables in filamentous fungi, the exact organization and dynamics of actin cables has remained elusive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 79 publications
(114 reference statements)
2
33
0
Order By: Relevance
“…In order to study the potential implications of the AP-1 complex in these processes, we monitored the localization of specific established apical and collar markers in conditions where the ap-1 σ expression has been fully repressed. These markers include the secretory v-SNARE SynA and t-SNARE SsoA (Taheri-Talesh et al, 2008), the phospholipid flippases DnfA and DnfB that partially localize in the Spk (Schultzhaus et al, 2015), the class III chitin synthase ChsB known to play a key role in hyphal tip growth and cell wall integrity maintenance (Yanai et al, 1994; Takeshita et al, 2015), the tropomyosin TpmA decorating actin at the Spk and on actin cables at the hyphal tip (Taheri-Talesh et al, 2008), and finally the endocytic patch specific marker AbpA marking the sites of actin polymerization (Araujo-Bazán et al, 2008), along with the endocytic markers SlaB and SagA (Araujo-Bazán et al, 2008; Hervás-Aguilar and Peñalva, 2010; Karachaliou et al, 2013). Additionally, we also tested the localization of the UapA xanthine-uric acid transporter, for which our previous work suggested that it is not affected by the loss of function of the AP-1 complex (Martzoukou et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to study the potential implications of the AP-1 complex in these processes, we monitored the localization of specific established apical and collar markers in conditions where the ap-1 σ expression has been fully repressed. These markers include the secretory v-SNARE SynA and t-SNARE SsoA (Taheri-Talesh et al, 2008), the phospholipid flippases DnfA and DnfB that partially localize in the Spk (Schultzhaus et al, 2015), the class III chitin synthase ChsB known to play a key role in hyphal tip growth and cell wall integrity maintenance (Yanai et al, 1994; Takeshita et al, 2015), the tropomyosin TpmA decorating actin at the Spk and on actin cables at the hyphal tip (Taheri-Talesh et al, 2008), and finally the endocytic patch specific marker AbpA marking the sites of actin polymerization (Araujo-Bazán et al, 2008), along with the endocytic markers SlaB and SagA (Araujo-Bazán et al, 2008; Hervás-Aguilar and Peñalva, 2010; Karachaliou et al, 2013). Additionally, we also tested the localization of the UapA xanthine-uric acid transporter, for which our previous work suggested that it is not affected by the loss of function of the AP-1 complex (Martzoukou et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…All collar-associated markers (SagA, SlaB and AbpA) appear “moved” in an acropetal manner towards the hyphal tip. TpmA has also lost its proper localization at the hyphal tip, suggesting defective stabilization of actin filaments at the level of the Spk (Bergs et al, 2016). For relative quantification of fluorescence intensity see also Figure 2 Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional cargo secretion in A. nidulans and other eukaryotes is known to be microtubule and actin network dependent (27,28). To investigate whether UapA secretion is dependent on distinct components of the cytoskeleton, we used drugs that block microtubule (benomyl) or actin (latrunculin B) organization.…”
Section: Uapa Sorting To the Pm Is Microtubule Independent But Actinmentioning
confidence: 99%
“…In fungi, polarization extends continuously at the hyphal apices, where lipids, mRNAs, vacuoles, peroxisomes and secretory vesicles are continuously transported to support cell wall and membrane extension (Bergs et al, 2016;Bi and Park, 2012;Desnos et al, 2007;Fischer et al, 2008;Giraldo et al, 2013;Hammer and Sellers, 2012;Pruyne et al, 2004;Riquelme, 2013;Takeshita, 2016). These organelles and cargoes are moved along the cytoskeleton by three classes of molecular motors: dyneins, kinesins and myosins (Hammer and Sellers, 2012).…”
Section: Introductionmentioning
confidence: 99%